Strategies for Developing Viable Microfinance Institutions with Sustainable Services: The Asian Experience - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1999)
In most developing countries, access to financial services by all segments of the population, including low-income people, is a matter of growing concern. Many governments have responded positively to this concern by embarking on financial system reform. They have attempted to match people?s demand for adequate financial services with the government?s responsibility for macroeconomic stability and a sound financial infrastructure. This endeavor includes: – deregulating the interest rate (or profit-sharing) regime; – adjusting the legal environment and create appropriate legal forms for MFIs; – transforming financial institutions into profitable intermediaries between savers and investors; – providing opportunities for local people to establish their own local financial institutions; – encouraging sound banking practices. However, these noble objectives have not been always pursued with the necessary vigor. This, at least, is the chief lesson from the Asian financial crisis, which is rooted in: – hazardous, politically instigated lending; – inadequate internal resource mobilization and unhedged external debts; and, above all, – inadequate regulation and supervision of financial institutions. As a result of soaring inflation rates, many poor people have lost their savings and, due to the illiquidity of financial institutions, their access to credit has been curtailed. The devasting effects of the recent financial crisis in East and Southeast Asia have lent additional emphasis to the crucial question of how to promote and prudentially regulate viable financial institutions with sustainable financial services with an outreach to all segments of the population including low-income people , in order to prevent such a financial crisis in other countries.
Keywords: 330; Mikrofinanzierung; Entwicklungsländer